Analisis Kestabilan Lereng Tambang Batubara pada Kondisi Statis dan Dinamis di PIT P3000 Block20, PT Trubaindo Coal Mining - Marzel Hizkia Zefanya (Fakultas Teknik, 2025)
This study focuses on the slope area of the P3000 Block20 pit at PT Trubaindo Coal Mining, a company operating in Kecamatan Melak, Kabupaten Kutai Barat, Provinsi Kalimantan Timur with coal commodities. The slope in a mining operation is a crucial aspect of open-pit mining. The background of this research involves analyzing slope stability under static and dynamic conditions and providing recommendations for good slope maintenance in the P3000 Block20 area. The study aims to present the current slope stability condition at the P3000 Block20 pit, determine the safety factor values, and offer slope maintenance recommendations to ensure safety and stability. The slope safety factor values were calculated using the limit equilibrium methods, specifically the Bishop, Janbu, and Morgenstern-Price methods, with Mohr-Coulomb failure criteria. The pit slope design was obtained from modeling, followed by slope stability analysis. The results using the limit equilibrium methods show that the safety factor under static conditions ranges from 1.5 to 1.664. Under dynamic conditions, safety factor ranges from 1.451 to 1.662. These results represent the safety factor range for each slope segment, lowwall and highwall, for each limit equilibrium method. There is a difference in safety factor values between static and dynamic conditions caused by parameters in dynamic conditions, such as blasting vibrations and vibrations from mining activities, which can influence slope stability. Despite this, the safety factor values are categorized as stable according to Keputusan Menteri ESDM Nomor 1827 K/30/MEM/2018. The recommendations to maintain slope stability include regular monitoring, verifying the actual field conditions with the slope design, supported by geotechnical monitoring instruments.
FINALISASI oleh Arif 2026 Juni 11
Keywords: Slope stability; safety factor; Limit Equilibrium Method; Coal